2017
DOI: 10.5539/mas.v11n9p75
|View full text |Cite
|
Sign up to set email alerts
|

A Modelling Framework to Design Executable Logical Architecture of Engineering Systems

Abstract: Modern production, logistic and assembly systems comprise of a considerable number of processes which operate by using diverse types of resources. Conceptual design of these systems has become more complicated because of the large scale and multi-disciplinary essence of their design knowledge. This paper proposes a modelling framework to support the conceptual design of such systems. The framework employs the principles of system engineering to fulfil the necessity of having a multi-disciplinary approach for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…The alternative generation algorithm generates alternatives by exploring the stored design-objects in the design knowledge database [53]. The algorithm uses an array of variables, which each represents a DR with a unique ID, see Eq.…”
Section: Alternative Generation and Feasibility Checking Algorithmsmentioning
confidence: 99%
See 1 more Smart Citation
“…The alternative generation algorithm generates alternatives by exploring the stored design-objects in the design knowledge database [53]. The algorithm uses an array of variables, which each represents a DR with a unique ID, see Eq.…”
Section: Alternative Generation and Feasibility Checking Algorithmsmentioning
confidence: 99%
“…'System-fuzzy-model': At the system level, certain processes can be more important due to their major impact on objectives' satisfaction. In the warehousing domain, the storing process is very critical and its design directly impacts the warehouse performance [53]. Thus, three input fuzzy sets are defined for 'system-fuzzy-model': 'Goodness' of processes (output of 'Process-fuzzy-model'), processes' importance, and objectives' importance.…”
Section: Fuzzy Modelsmentioning
confidence: 99%
“…The development process of system architecture is presented in Figure 3. In summary, it can be found that the primary purpose of building an architecture for an autonomous system is essential, and essential especially for designing the overall structure and realizing the expected functions of the system, which, in turn, enhances the autonomous and task fulfillment abilities of the system [40]. For an autonomous system, four kinds of abilities, including environment perception and self-perception, planning, self-execution, and self-learning ability promising self-adaptation and self-evolution.…”
Section: Composition Of Architecturementioning
confidence: 99%
“…Generally speaking, after stakeholders propose their cooperative capability requirements, modelers will abstract the requirements and design models. Since stakeholders' requirements are usually textual descriptions expressed by human-readable nature languages, there will be several semantic or inconsistency gaps between the modeling language and the natural language [4]. During various modeling languages in the modeling domain at present, the unified modeling language (UML) [8], released by the Object Management Group (OMG), is considered as a popular and practical modeling standard in actual industry modeling practice [9], and especially is widely used to describe the architecture of some large and complex systems in the specific domain [10].…”
Section: How To Define the Associations Between Elements (Or Concepts...mentioning
confidence: 99%